Answer:
x = -3
y = -13
Step-by-step explanation:
There are many ways you can solve these types of questions:
x = 10 + y ... 1
y = 6x + 5 ... 2
You can sub y = 6x + 5 into the first equation
Hence, x = 10 + 6x + 5
Simplify
-5x = 15
x = -3 ===> sub this value into any equation ...1 or ...2 (I'm going to go with 1)
-3 = 10 + y
-3 - 10 = y
y = -13
Another way: Rearrange the first equation so that it would be y = x - 10
Then the two equations would be:
y = x - 10 ... 3
y = 6x + 5 ... 4
Since they both equal y and y has to be the same value, these two equations would equal each other.
Hence, x - 10 = 6x + 5
Rearrange: x - 6x = 5 + 10
-5x = 15
x = -3
Sub the value of x into ....3 or ....4 and you would get y = -13